Nosocomial Infections During Extracorporeal Membrane Oxygenation: Incidence, Etiology, and Impact on Patients' Outcome - Grasselli, Giacomo; Scaravilli, Vittorio; Di Bella, Stefano; Biffi, Stefano; Bombino, Michela; Patroniti, Nicolò; Bisi, Luca; Peri, Anna Maria; Pesenti, Antonio; Gori, Andrea; Alagna, Laura (Critical care medicine, 2017)
To study incidence, type, etiology, risk factors, and impact on outcome of nosocomial infections during extracorporeal membrane oxygenation. Retrospective analysis of prospectively collected data. Italian tertiary referral center medical-surgical ICU. One hundred five consecutive patients who were treated with extracorporeal membrane oxygenation from January 2010 to November 2015. None. Ninety-two patients were included in the analysis (48.5 [37-56] years old, simplified acute physiology score II 37 [32-47]) who underwent peripheral extracorporeal membrane oxygenation (87% veno-venous) for medical indications (78% acute respiratory distress syndrome). Fifty-two patients (55%) were infected (50.4 infections/1,000 person-days of extracorporeal membrane oxygenation). We identified 32 ventilator-associated pneumonia, eight urinary tract infections, five blood stream infections, three catheter-related blood stream infections, two colitis, one extracorporeal membrane oxygenation cannula infection, and one pulmonary-catheter infection. G+ infections (35%) occurred earlier compared with G- (48%) (4 [2-10] vs. 13 [7-23] days from extracorporeal membrane oxygenation initiation; p < 0.001). Multidrug-resistant organisms caused 56% of bacterial infections. Younger age (2-35 years old) was independently associated with higher risk for nosocomial infections. Twenty-nine patients (31.5%) died (13.0 deaths/1,000 person-days of extracorporeal membrane oxygenation). Infected patients had higher risk for death (18 vs. 8 deaths/1,000 person-days of extracorporeal membrane oxygenation; p = 0.037) and longer ICU stay (32.5 [19.5-78] vs. 19 [10.5-27.5] days; p = 0.003), mechanical ventilation (36.5 [20-80.5] vs. 16.5 [9-25.5] days; p < 0.001), and extracorporeal membrane oxygenation (25.5 [10.75-54] vs. 10 [5-13] days; p < 0.001). Older age (> 50 years old), reason for connection different from acute respiratory distress syndrome, higher simplified acute physiology score II, diagnosis of ventilator-associated pneumonia, and infection by multidrug-resistant bacteria were independently associated to increased death rate. Infections (especially ventilator-associated pneumonia) during extracorporeal membrane oxygenation therapy are common and frequently involve multidrug-resistant organisms. In addition, they have a negative impact on patients' outcomes.